2011
DOI: 10.1208/s12249-011-9640-z
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Correlation of the Effect of Density Distributions in Roller-Compacted Ribbons on the Mechanical Properties of Tablets Using Ultrasonics and X-ray Tomography

Abstract: Enabling the paradigm of quality by design requires the ability to quantitatively correlate material properties and process variables to measureable product performance attributes. In this study, we show how heterogeneities in compacted ribbon densities quantitatively correlate to tablet mechanical properties. These density variations, which have been purposely modulated by internal and external lubrications, are characterized longitudinally and transversally by nondestructive ultrasonic and X-ray micro-comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Recent studies demonstrate that the compression pressure in the middle of ribbon width is higher than that at the edges (9). The density variations in roller compacts have been recently investigated with ultrasonic testing and X-ray tomography (10). A recent study demonstrates the density distribution along the ribbon by analyzing off-line images of MCC ribbons obtained via near-infrared (NIR) chemical imaging (11).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrate that the compression pressure in the middle of ribbon width is higher than that at the edges (9). The density variations in roller compacts have been recently investigated with ultrasonic testing and X-ray tomography (10). A recent study demonstrates the density distribution along the ribbon by analyzing off-line images of MCC ribbons obtained via near-infrared (NIR) chemical imaging (11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Glass and Ewsuk (1995) used ultrasound to determine relative density of alumina compact. Akseli et al (2011) used both ultrasound and X-ray CT to determine density distribution of ribbon compacted microcrystalline cellulose in investigation of mechanical properties. They showed that both methods have resolution to distinguish spatially distributed density in compacts.…”
Section: Quality; Density and Density Distributionmentioning
confidence: 99%
“…These tablets were also analyzed for tensile strength determined from the crushing strength data (UK200, VanKel, Manasquan, USA) as reported previously [9]. Tablets were then passed through an oscillating granulator (Riddhi Pharma Machinery, India) fitted with a # 20 sieve (840 µm pore size), analyzed for particle size, porosity and densities.…”
Section: Powder Characterizationmentioning
confidence: 99%
“…This granulation is desirable for heat or moisture sensitive drugs [8]. The characteristics of the granules produced by direct compression and wet granulation influence compact hardness, disintegration and drug dissolution [9,10]. If hydrophobic drugs are used, hydrophilic liquids can be added during wet granulation to wet a powder blend to facilitate tablet disintegration and drug dissolution [11][12][13][14] On the other hand, sometimes formulation scientists have to face problems related with manufacture of compacts due to changes in crystallinity, porosity, hygrospicity, particle size which have a deleterious effect on critical manufacturing properties such as flow, compressibility and compactibility of excipients or drug:excipients mixtures.…”
Section: Introductionmentioning
confidence: 99%